2016
DOI: 10.1186/s13638-016-0582-8
|View full text |Cite
|
Sign up to set email alerts
|

Compressive sensing based joint frequency offset and channel estimation for OFDM

Abstract: We consider joint estimation of carrier frequency offset (CFO) and channel impulse response (CIR) for orthogonal frequency division multiplexing (OFDM) with pilot symbols. A new method based on compressed sensing is proposed. It has been shown that the CIR can be represented as a 1-block sparse signal by using a dictionary constructed by concatenating subspaces of CFO values taken from a search space. Recovery of both CFO and CIR is accomplished by the block orthogonal matching pursuit algorithm. The proposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…From Equation (4), the corresponding pilot vectors of the m-th received OFDM symbol can be obtained as 20) is the ICI item. Substituting Equation (19) into Equation (20), and then performing simple algebraic manipulations, we can obtain…”
Section: The Dcs Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…From Equation (4), the corresponding pilot vectors of the m-th received OFDM symbol can be obtained as 20) is the ICI item. Substituting Equation (19) into Equation (20), and then performing simple algebraic manipulations, we can obtain…”
Section: The Dcs Formulationmentioning
confidence: 99%
“…The second term on the right-hand side of Equation ( 20) is the ICI item. Substituting Equation (19) into Equation (20), and then performing simple algebraic manipulations, we can obtain…”
Section: The Dcs Formulationmentioning
confidence: 99%
“…Sparsity pattern estimation is carried out using the version of the BPDN algorithm detailed in Section III-A with σ 2 = 1.05 · E w 2 and = 0.005. For the RCS-AML estimator (12), if |K|> N 0 , then K is truncated to contain only the indexes corresponding to the N 0 most dominant entries ofh. We consider two values of N obs corresponding to N p ∈ {4, 6}.…”
Section: Numerical Examples and Discussionmentioning
confidence: 99%
“…Indeed, in [4], it was shown that applying CS improves the performance of CIR estimation for wireless channels as well as the spectral efficiency. The works [11], [12] proposed a CS-based joint CIR and CFO estimator for slow-fading wireless LTI channels with AWGN. However, in [11] it was assumed that the number of non-zero CIR coefficients is a-priori known, and in [12] it was assumed that the number of observations is larger than the number of estimated parameters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation